Core-shell Nanoparticles Based on Polystyrene and Poly(n-butyl acrylate) Functionalized with Itaconic Acid for Baroplastic Processing - Fernanda Furtado de Melo Albino; Jacira Aparecida Castanharo; João Batista Lourenço Neto; Marcos Antonio da Silva Costa (Materials Research)
Core-shell polymer nanoparticles with poly(n-butyl acrylate) core and polystyrene shell can be produced by emulsion polymerization. These materials exhibit baroplastic behavior that allows them to be processed at low temperatures by compression molding or extrusion. In this work, core-shell copolymers of poly(n-butyl acrylate) cores and polystyrene shells were synthesized in a two-stage emulsion polymerization. The addition of itaconic acid as functional monomer in the core polymerization was carried out in order to study its influence on polymer processing and mechanical properties. The copolymers were characterized by dynamic light scattering (DLS), transmission electronic microscopy (TEM), infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The functional monomer incorporation was confirmed by DSC and quantified by titration. The poly(n-butyl acrylate) and polystyrene proportions had a direct influence on the polymer processing and mechanical properties. Copolymers with polystyrene contents higher than 50% presented baroplastic behavior and they could be processed at room temperature by compression molding and extrusion. The presence of itaconic acid did not affect polymer processing and significantly improved tensile resistance, increasing its toughness.